2007
DOI: 10.1016/j.jacc.2006.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes After Management of Restenosis or Thrombosis of Drug-Eluting Stents

Abstract: Current treatments of ISR or STH in DES are associated with a high long-term rate of MACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 13 publications
3
71
0
1
Order By: Relevance
“…842,843 Patients with clinical restenosis typically present with recurrent exertional angina, but 5% to 10% of patients present with acute MI and 25% with UA. 844,845 Factors associated with an increased risk of restenosis in various models include clinical setting (STEMI, ACS, daily angina), patient characteristics (diabetes, age Ͻ55 to 60 years, prior PCI, male sex, multivessel CAD), lesion location (unprotected left main, SVG), and procedural characteristics (minimum stent diameter Յ2.5 mm, total stent length Ն40 mm). 778,846 PCI strategies for treating restenosis after balloon angioplasty, BMS, and DES are reviewed in the following sections.…”
Section: Background and Incidencementioning
confidence: 99%
“…842,843 Patients with clinical restenosis typically present with recurrent exertional angina, but 5% to 10% of patients present with acute MI and 25% with UA. 844,845 Factors associated with an increased risk of restenosis in various models include clinical setting (STEMI, ACS, daily angina), patient characteristics (diabetes, age Ͻ55 to 60 years, prior PCI, male sex, multivessel CAD), lesion location (unprotected left main, SVG), and procedural characteristics (minimum stent diameter Յ2.5 mm, total stent length Ն40 mm). 778,846 PCI strategies for treating restenosis after balloon angioplasty, BMS, and DES are reviewed in the following sections.…”
Section: Background and Incidencementioning
confidence: 99%
“…However, in the present study, lesion complexity, including quantitative coronary angiography results, was not less than that in previous registries. [4][5][6][7][8] Furthermore, routine angiographic follow-up might be associated with a higher incidence of focal restenosis. However, clinical presentation at follow-up angiography in the present study did not differ between patients with focal and non-focal restenosis.…”
Section: Angiographic Restenosis Pattern After Des Implantationmentioning
confidence: 99%
“…1-10 Large-scale randomized trials 1-3 have demonstrated a high proportion of focal restenosis after DES implantation, but on the other hand, recent real-world registries have shown that a significant proportion of restenosis is non-focal when DES are used in unselected lesions. [4][5][6][7][8] The present study evaluated angiographic patterns of restenosis after sirolimuseluting stent (SES) implantation in real-world practice in Japan. …”
mentioning
confidence: 99%
“…Furthermore, current therapies for DES ISR or DES thrombosis are associated with a high long-term rate of MACE (42.9%). 18 The present study prospectively discovered that repeated SES implantation to treat SES restenosis is associated with a higher incidence of late restenosis, ischemiadriven TLR and MACE than SES implantation to treat BMS restenosis. The rates of re-restenosis, TLR or MACE in the present study were relatively similar to the findings of several retrospective studies.…”
Section: Discussionmentioning
confidence: 66%